Platelet Count and its Correlation with Blood Sugar Level in Type 2 Diabetes Mellitus Patients (International Journal of Physiology, 2019)
IntroductionDiabetes Mellitus (DM) is defined as a complex disease with chronic hyperglycemiaand is a global public health problem; the long-term sequelae of which are long-term macrovascular and microvascular complications. Studies show role of hematological indices especially platelet indices in contributing to the vascular injury in diabetic patients. Thus, the aim of this study was to determine platelet indices and their correlation with fasting blood glucose levelin type 2 DM patients in comparison with healthy controls.MethodA retrospective study was conducted at DM Wayanad Institute of Medical Sciences, Kerala, India from Istof January 2018 to 31st of June. A total of 238 participants (119 cases and 119 healthy controls) were selected using systematic random sampling technique. Data is retrieved from Medical Records Department. Parameters are lab investigation values those are already done on patients who came to DM WIMS. FBS was estimated using (Cobasintegra 400 plus) automated clinical chemistry analyzer and hematological parameters using fully automated (Sysmex XT-1800i) analyzer. Independent sample t-test. The sample size required to study the correlation is 90 at 5% level of significance and 80% power assuming the population correlation to be. 3 (moderate correlation). The statistical analysis was done using SPSS 15.0 version. After checking for normality Pearson's or Spearman correlation analysis is carried out to study the correlation. A P-value, 0.05 was considered as statistically significant.ResultThere was no significant correlation between platelet indices, mean platelet volume, platelet distribution width in the diabetic patients.ConclusionEven though previous study showed statistically significant difference in platelet indices of diabetic patients compared to controls in our study there is no such statistical significance. Further studies should be done in large population.